Der Einfluss von natürlichem Aerosol auf Wolken über Mitteleuropa - Rieger, Daniel (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2017)
This work studies the interaction of natural aerosol with clouds for two different weather regimes in Central Europe. One model study highlights the impact of sea salt aerosol on postfrontal, convective cumulus clouds. The other study examines the influence of mineral dust aerosol on the formation of cirrus clouds during a mineral dust outbreak on 3 April 2014.